2010
DOI: 10.4028/www.scientific.net/kem.447-448.695
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of AZ91D Magnesium Alloy Using Millisecond, Nanosecond and Femtosecond Lasers

Abstract: Poor surface properties of magnesium alloys limit their extensive use in many applications. Laser surface engineering can be used to enhance surface-related properties of Mg alloys, and the purpose of this paper is to study the effect of laser pulse duration on surface of AZ91D Mg alloy. After millisecond-pulse laser treatment, ripples and cellular/dendrite as well as nanoscale -Mg17Al12 precipitates in the -Mg matrix were found in the surface microstructure, moreover, the melt depth was more than 150 micron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Mg alloys are important engineering materials, and they are widely used in automobile, communication and aerospace industries due to low density and high specific strength. In order to improve their poor surface-related properties, it has been demonstrated that laser surface treatment can be used to further extend the applications of Mg alloys [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Mg alloys are important engineering materials, and they are widely used in automobile, communication and aerospace industries due to low density and high specific strength. In order to improve their poor surface-related properties, it has been demonstrated that laser surface treatment can be used to further extend the applications of Mg alloys [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Considerable effort has been made in the past decade or so to study casting [1,2,3], welding [4], machining [5,6], heat treatment [7,8], phase transformation [9], surface coating [10,11], and laser processing [11,12,13,14,15,16] of various magnesium alloys, including AM50A [5,17], AM60 [1], AZ31B [18], AZ91D [4,7,8,9,10,11,12,13,14,15,16], and Mg-based composites [19,20]. Effort has also been made to study the materials' corrosion mechanisms [7,18,20,21,22,23], biocorrosion behavior [8,13], wear resistance [24], fatigue properties [25] and fracture under dynamic loading [17].…”
Section: Introductionmentioning
confidence: 99%
“…3 shows typical solidification microstructure of AZ91D Mg alloy irradiated with nanosecond pulse Nd:YAG laser. As shown inFigure 7.3 (a),…”
mentioning
confidence: 99%